2015
DOI: 10.1002/pmic.201500339
|View full text |Cite
|
Sign up to set email alerts
|

Capillary zone electrophoresis for bottom‐up analysis of complex proteomes

Abstract: Capillary zone electrophoresis (CZE) is emerging as a useful tool in proteomic analysis. Interest arises from dramatic improvements in performance that result from improvements in the background electrolyte used for the separation, the incorporation of advanced sample injection methods, the development of robust and sensitive electrospray interfaces, and the coupling with Orbitrap mass spectrometers with high resolution and sensitivity. The combination of these technologies produces performance that is rapidly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…Advancements in RPLC column technology allow ultraperformance liquid chromatography (UPLC) systems to run at nanoflow rates in columns packed with 1.7μm C18 particles, which greatly enhances the resolution and sensitivity of the separation 46, 47 . CZE is an increasingly popular method that provides complementary identification of analytes to UPLC 48, 49 . This method separates molecules based on their mass-to-charge ratio is often able to detect hydrophilic molecules that are weakly retained on reversed-phase columns.…”
Section: Mass Spectrometry For Biological Studiesmentioning
confidence: 99%
“…Advancements in RPLC column technology allow ultraperformance liquid chromatography (UPLC) systems to run at nanoflow rates in columns packed with 1.7μm C18 particles, which greatly enhances the resolution and sensitivity of the separation 46, 47 . CZE is an increasingly popular method that provides complementary identification of analytes to UPLC 48, 49 . This method separates molecules based on their mass-to-charge ratio is often able to detect hydrophilic molecules that are weakly retained on reversed-phase columns.…”
Section: Mass Spectrometry For Biological Studiesmentioning
confidence: 99%
“…Recent improvements in coupling CZE to MS/MS aimed to bridge the gap between CE and RP-HPLC in combination with tandem mass spectrometry analysis [2831]. Sun et al [28] reported the identification of over 10,000 peptides and 2,100 proteins in a single pass analysis of tryptic digest of HeLa cells – almost an order of magnitude improvement from previously reported studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews highlight the use of CZE and CE-ESI-MS for bottom-up proteomics, 18, 19, 143, 144 and CE and MCE methods for top-down proteomics including investigation of post-translational modifications (PTMs). 18 These reviews include advances that have been made for CE interfacing to ESI-MS, electrospray ionization-tandem mass spectrometry (ESI-MS/MS), and matrix-assisted laser desorption/ionization mass spectrometry (MADLI-MS).…”
Section: Applications Of Ce and Mcementioning
confidence: 99%
“…Recent review articles have been published highlighting protein analyses by CE, 16 MCE, 17 and in proteomics. 18, 19 Our review highlights the most important developments regarding protein analysis using CE and MCE. Specifically, new advances in overcoming protein adsorption for CE and MCE methods, the use of various CE modes for protein analysis, the development of novel materials for MCE, interfacing CE with MS detection for protein analysis, further enhancements in preconcentration technique for improved sensitivity, and developments of CE/MCE in the applications of proteomics and protein therapeutics.…”
Section: Introductionmentioning
confidence: 99%